Assessment of worm control practices recommended by equine veterinarians in Australia - Abbas, Ghazanfar; Stevenson, Mark A.; Bauquier, Jenni; Beasley, Anne; Jacobson, Caroline; El-Hage, Charles; Wilkes, Edwina J. A.; Carrigan, Peter; Cudmore, Lucy; Hurley, John; Beveridge, Ian; Nielsen, Martin K.; et al. (Frontiers in Veterinary Science, 2023)
This study aimed to assess Australian veterinarians' knowledge, perceptions and treatment strategies for worm control in horses with an online questionnaire. The questionnaire comprised 64 questions covering various aspects of: (i) veterinary practice; (ii) the veterinarian's knowledge of gastrointestinal nematodes (GINs) and the importance of parasites in different age groups of horses; (iii) the diagnosis and control of worms; (iv) anthelmintics and anthelmintic resistance (AR,) (v) grazing management; and (vi) the means of communication and the discussion between veterinarians and their clients regarding worm control. Following a pilot survey, a link for the questionnaire survey was sent to all (n = 1,148) registered members of Equine Veterinarians Australia in April 2020. The response rate for the questionnaire was 10% (118 of 1,148). The findings of this study illustrate veterinarians' good understanding of aspects of equine parasites, including control. However, respondents mainly recommended frequent, interval-based prophylactic deworming in young horses, and only 40% (96 of 239) diagnosed GIN infections based on faecal egg count (FEC) results in all age groups of horses. Furthermore, only 27% (88 of 330) of the respondents made deworming decisions based on FECs. Most of the respondents recommended MLs for all age groups of horses (71%, 481 of 677), and the most frequently used method to calculate the dose of anthelmintics was by estimating the weight of animals visually (53%, 63 of 118). Although the majority of respondents (97%, 115 of 118) perceived AR to be a critical issue in managing worms in horses, 58% (67 of 118) of them were unaware of the status of AR on their clients' properties. Forty-two percent (50 of 118) of the respondents perceived the presence of AR in worms, including pinworms (16%), strongylins (15%), species of Draschia and Habronema (6%), Strongyloides westeri (2%) and tapeworms (1%). Twenty-seven percent (32 of 118) of the respondents rarely discussed equine worm control practices with their clients. This study provides insights into the perception and worm control practices recommended by Australian veterinarians to manage equine parasites.